TINJAUAN ANALISIS HIDROLOGI BENDUNG MENCONGAH KECAMATAN LINGSAR KABUPATEN LOMBOK BARAT - YOHANIS DAPPA; MUHAMAD YAMIN; BAIQ RENI SARI DEWI (SOSIAL SAINS DAN TEKNOLOGI, 2022)
The purpose of this study was to determine the availlability of water that can be used for irrigation water needs in the mencongah weir irrigation area and to determine the amoun of irrigation water demand in mencongah weir and to determine the planned discharge of mencongah dam rainfall data from 2011 to 2020. The evailbality of water at mencongah weir during the planting season with a planting period  0f 4 (four) times is still fulfilled with Q mak = 14.090 lt/ sec/ha. Water needs of Q =11,272 lt/sec/ha , the water requirement of the mencongah weir according to the analysis  results obtained a minimum discharge of =1,275 lt/ sec/ ha while the minimum water requirement of Qmin =1.02 lt/ sec/ha the demand and availabilyti of the mencongah weir was fulfilled during the growing season take place .